Back Analysis dan Validasi Numerik-Manual Parameter Residual Soil: Studi Kasus Longsoran Bendungan Bagong - Al Qorni, Muhammad Rizqi Uwais; Sadono, Kresno Wikan; Sukamta, Sukamta (Jurnal Talenta Sipil, 2026)
A landslide on the left abutment of the Bagong Dam on 14 August 2025 indicated a significant gap between the design parameters and the actual field conditions, particularly within the critical zone of weathered limestone and residual soil (RQD = 0–11%). This study aims to validate the geotechnical parameters of the dam abutment through back analysis of the actual landslide and to formulate safe slope geometry design recommendations. A comprehensive research methodology is employed, integrating geological characterization based on six boreholes, parametrized back analysis using ten reference materials with similar geological conditions, cross-method validation between the Limit Equilibrium method (manual Fellenius method) and the finite element method (PLAXIS LE), GSI–Hoek–Brown validation for weathered rock zones, and parameter sensitivity analysis. The results show that the validated parameters c = 35,5 kPa and φ = 23° represent the critical field conditions, yielding safety factors of FS = 1,173 (PLAXIS LE) and FS = 1,2588 (Fellenius method), with an inter-method deviation of 7,32%. Sensitivity analysis identifies the pore pressure ratio (Ru) as the dominant controlling factor (ΔFS/ΔRu = –0,155), explaining the failure mechanism during the rainy season. The optimal design recommendation is a stepped slope geometry with a single berm at elevation 320 m and a slope angle of 33°, resulting in FS = 1,629, which satisfies construction safety criteria (FS ≥ 1,35) and represents a 38,8% increase in stability compared with the existing condition.